Hypervitaminosis B12 - Koprivica, Marko M; Bjelanović, Jelena (Medicinski časopis, 2022)
Increased concentrations of vitamin B12 are the result of excessive intake of this vitamin, increased release of vitamins from hepatic depots, or elevated concentrations of transcobalamin resulting from the increased production or reduced decomposition of this molecule. The most common diseases that lead to B12 hypervitaminosis are malignancies and solid tumours. As a result of elevated concentrations, acnes emerge or exacerbate the already existing acneiform changes. Rosacea fulminant, allergic, and other anaphylactic reactions may also develop. The aim of the study was to determine the effect of increased concentrations of vitamin B12 onto human health. In a study conducted by Deneuvil and associates, the elevated B12 vitamin levels were observed in 12% of respondents. In the study by Carmel and associates, 14% of the respondents had high cobalanemia. The results of other studies show that the prevalence of high cobalanemia is 13%, while very high cobalanemia is registered in 7% of cases. In the multicentric BDOSE study, the incidence of high serum cobalamin was 18%. The increased concentrations of cobalamin are most commonly caused by a disease, while disorders due to inadequate intake and overdose are much less common. As a result of B12 hypervitaminosis, acnes emerge or exacerbation of the pre-existing acneiform changes may occur. In addition to acne, other dermatological diseases (Rosacea fulminant, dermatitis) may develop as a result of hypervitaminosis, followed by allergic and anaphylactic reactions.